Pengaruh Self Management Terhadap Kedisplinan Mahasiswa Bimbingan Konseling Islam - Nadiyatu Rahmah; Isak Iskandar (PT. Hasba Edukasi Mandiri, 2025)
This study aims to determine the effect of self-management on the learning discipline of students in the Islamic Guidance and Counseling Study Program at the Sultan Maulana Hasanuddin State Islamic University, Banten. Self-management in this context includes students' ability to manage time, maintain motivation, control themselves, and plan academic activities in a focused manner. Learning discipline is measured by consistency of attendance, accuracy in completing assignments, and compliance with academic rules. This study uses a quantitative correlational approach with a sample size of 30 students selectea through purposive sampling techniques. The instrument used was a Likert scale questionnaire to measure self-management and learning discipline. The results showed that there was a significant relationship between self-management ano learning discipline. Students with a high level of self-management tend to have better learning discipline. Self-management has been shown to provide a positive contribution to increasing disciplined behavior in academic activities. These findings indicate that strengthening self-management skills is one of the main keys in shaping the character of students who are responsible, organized, ano ready to face academic and professional challenges. Therefore, it is important for educational institutions to provide early self-management skills training.